2011
DOI: 10.1182/blood.v118.21.5049.5049
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact of Myelodysplasia (MDS) From the Patients' Perspective

Abstract: 5049 Introduction: Little research is currently available on the impact of MDS from the patients' perspective. Where research has been conducted it has predominantly used generic cancer outcome measures. Such measures do not provide an accurate assessment of MDS patients as they miss important aspects of the condition. A qualitative study was conducted with MDS patients to investigate how their lives are affected by the condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Shortness of breath was the second most common and bothersome symptom reported by participants, also consistent with the findings of prior qualitative research [ 25 , 43 , 47 ]. Weakness and low energy were also reported to be most bothersome by a few patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Shortness of breath was the second most common and bothersome symptom reported by participants, also consistent with the findings of prior qualitative research [ 25 , 43 , 47 ]. Weakness and low energy were also reported to be most bothersome by a few patients.…”
Section: Discussionsupporting
confidence: 89%
“…Other symptoms that were reported by patients included pain, bruising, bleeding, infections, fever, and heart palpitations. In line with the literature, participants described a significant impact of these symptoms on ADLs and physical functioning [ 31 , 41 , 43 , 46 , 48 , 49 ]. Most of these impacts were attributed to fatigue/tiredness, shortness of breath, weakness and low energy, further supporting the finding that participants reported these symptoms as most bothersome.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…There were six studies within seven citations eligible for inclusion within this review. One of these studies is due to start recruiting patients, and the other has not yet been published in full (http://onlinelibrary.wiley.com/doi/10.1111/trf.12441/suppinfo, available as supporting information in the online version of this paper). Of the completed studies, there was one RCT, one prospective observational study, one interview study, and one Web‐based survey (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Two authors responded and provided further unpublished information . The author of one of the ongoing studies confirmed that this has not yet been published in full …”
Section: Methodsmentioning
confidence: 91%